Pandangan Masyarakat Kecamatan Pantai Labu Terhadap Harta Bersama Sebagai Harta Warisan Perspektif Kompilasi Hukum Islam - Rinaldi, Fiqih; Radwan Siddik Turnip, Ibnu (UNES Law Review, 2023)
Talking about joint property in Indonesia and its relation to inheritance, it cannot be separated from reviewing the Compilation of Islamic Law, especially Article 96 paragraph (1) which emphasizes that in the event of a divorce, half of the joint property becomes the right of the spouse who lives longer. This study wants to know the views of the people of Pantai Labu District towards common property as heritage property which seems still not uniform when viewed from the perspective of the Compilation of Islamic Law. This research is an empirical legal research, using qualitative methods. Data collection techniques by observation and interviews with a number of informants from 5 (five) villages in Pantai Labu District. The results showed that the Compilation of Islamic Law, which had been formed in 1991, was still not fully implemented by the Muslim community in Pantai Labu, this can be seen by the difference in understanding in seeing the rules regarding joint property, half of which are the rights of the spouse left behind, in addition to the rights that have been determined in the inheritance law. There are two (2) people's understanding of common property, one understanding ignores the rules in Article 96 paragraph (1) of the Compilation of Islamic Law, on the other hand there is an understanding in accordance with these rules. In addition, it is also known the desire of some people who choose rules that benefit their position in heirs, and in terms of their control over inheritance.